2012
DOI: 10.1016/j.matchar.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The influence of quench sensitivity on residual stresses in the aluminium alloys 7010 and 7075

Abstract: The most critical stage in the heat treatment of high strength aluminium alloys is the rapid cooling necessary to form a supersaturated solid solution. A disadvantage of quenching is that the thermal gradients can be sufficient to cause inhomogeneous plastic deformation which in turn leads to the development of large residual stresses. Two 215 mm thick rectilinear forgings have been made from 7000 series alloys with widely different quench sensitivity to determine if solute loss in the form of precipitation du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 24 publications
3
40
1
Order By: Relevance
“…The difference in RS between single (311) diffraction peak and multiple peaks analysis is within the experimental uncertainty. This is in agreement with other studies [4]. The major difference between the three cases is the experimental uncertainty; it is around 10 MPa at SALSA, 30 MPa at POLDI using one peak and 50 MPa using Pawley analysis.…”
Section: Rs Analysissupporting
confidence: 92%
See 3 more Smart Citations
“…The difference in RS between single (311) diffraction peak and multiple peaks analysis is within the experimental uncertainty. This is in agreement with other studies [4]. The major difference between the three cases is the experimental uncertainty; it is around 10 MPa at SALSA, 30 MPa at POLDI using one peak and 50 MPa using Pawley analysis.…”
Section: Rs Analysissupporting
confidence: 92%
“…Robinson et al [4] who reported a decrease in stress free lattice parameter from the surface to the core of AA7075 thick forgings attributed to solute loss, no such variation is observed in the present work. 7449 and 7075 alloys being both quench sensitive, the difference is thought to originate from the different thickness of the components: 75 mm in the present case and 215 mm in [4].…”
Section: Rs Analysiscontrasting
confidence: 70%
See 2 more Smart Citations
“…When an area of the part which is on residual stress mode, is removed this causes an imbalance of the tensile/compressive layers (Hatamleh et al, 2009), thus, the part distorts to maintain a balance of compressive and tensile stresses. If the resulting residual stresses in the part are zero or very low, no movement occurs (Mandy et al, 2007); however, to achieve such a state, almost all the machining conditions must be chosen correctly (Robinson, 2012). Distortion is problematic in several ways.…”
Section: Introductionmentioning
confidence: 99%